Role of Adolescence Lifestyle in Cardio Vascular Disease-An Ayurvedic Perspective - Anoop AK,; Nithya AK,; Sandhya CV, (International Journal of Ayurveda and Pharma Research, 2021)
Heart disease in the adolescent age group has a unique spectrum. Among all adolescents, risk factors like obesity, an inactive lifestyle, smoking, high blood pressure, and high cholesterol that have a direct relationship on the probability of having cardiac disease later in life. According to Ayurvedic literature, Hridaya is the mula of RasavahaSrotas . The vitiation of this system may lead to diseases such as Sthoulya, Hridroga etc. The role of VyanaVayu and Ojus which contribute significantly to the health and disease of cardio-vascular system. Cardiac risk factors can be prevented or managed by lifestyle including principles of Dinacharya, Ritucharya and sadvrtta. With rapid economic development and increasing urbanization of lifestyle in the past few decades, prevalence of these diseases has reached alarming proportions among Indians in the recent years. So, this presentation is an effort to throw light on the role of adolescence life style in cardiac diseases.